Scabies prevalence and its associated factors among prisoners in southern Ethiopia: An institution-based analytical cross-sectional study. - Efa Ambaw Bogino; Beshada Zerfu Woldegeorgis; Lantesil Wondewosen; Blen Kassahun Dessu; Mohammed Suleiman Obsa; Lolemo Kelbiso Hanfore; Teketel Ermias Galtore; Woldu Kidane; Abraham Getachew Kelbore (PLoS Neglected Tropical Diseases, 2023)
Background Scabies is an ectoparasitic infestation that can easily spread during close human contact and in overcrowded areas such as prisons and public places where sanitation is a problem. Globally, as many as 300 million people are infested with scabies each year. Within Ethiopia, its burden in institutions like prisons is not well-studied. As a consequence, we sought to estimate the prevalence of scabies and also identify factors associated with it among prison inmates in southern Ethiopia. Methods An institution-based analytical cross-sectional study design was employed. We used, a simple random sampling technique to select 422 prisoners. A pretested-structured questionnaire was used to collect the necessary information. EpiData version 4.2.0.0 and Statistical Packages for Social Science version 25 software were used for data entry and analysis respectively. Both descriptive and inferential statistics were computed. The model fitness was checked using the Hosmer-Lemeshow and omnibus tests. The association between the independent and outcome variables was presented in the form of a table showing the crude odds ratio and adjusted odds ratio (AOR) along with their 95% confidence interval (CI). The level of statistical significance was declared at P.value ≤ 0.05. Results A total of 418 prisoners were interviewed, yielding a 99.1% response rate. The age of the participants ranged from 17 to 60 years. As many as 381 (91.1%) participants were male. The prevalence of scabies was found to be 8.9%. A history of sexual contact in the past two months, before imprisonment (AOR: 9.92 (95% CI 3.07, 32.02), P <0.001), a period of stay less than two months duration in the prison (AOR: 4.54 (95% CI 1.51, 13.54), P = 0.007), poor ventilation (AOR: 3.36 (95% CI 1.07, 10.58), P = 0.038), lack of hygiene soap (AOR: 5.53 (95% CI 1.45, 21.17), P = 0.012), and sharing clothes among each other (AOR: 3.81 (95% CI (1.09, 13.29), P = 0.036) were factors independently associated with a scabies infestation. Conclusion In this study, we found the prevalence of scabies was high among prison inmates in Wolaita Zone prison. Furthermore, scabies infestations were associated with a previous history of sexual contact, poorly ventilated rooms, lack of hygiene soaps for washing, and sharing clothes amongst the inmates. Prison administrations should be encouraged to improve sanitary and screening and isolation of prisoners during imprisonment.